2018
DOI: 10.22452/ajba.vol11no1.6
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of Performance Measurement System (PMS) Implementation in Indonesian Local Governments: Why is Their Performance Still Poor?

Abstract: Manuscript type: Research paper. Research aims: This study aims to investigate the Performance Measurement System implementation in Indonesian local governments and the phenomenon of institutional isomorphism. Design/ Methodology/ Approach: This paper employed a qualitative approach, using semi-structured interviews and observations. The samples comprise the heads of departments and individuals representing the agencies and institutions in the Yogyakarta Special Region. A deductive thematic method was utilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 20 publications
(50 reference statements)
4
33
0
6
Order By: Relevance
“…Even though community participation and the competency of village management are high, if these two factors are not able to create good village fund management, then it would not contribute to a better village autonomy. This idea is in line with the perspective of the institutional isomorphism mechanism DiMaggio & Powell (1983) as further elaborated by (Sofyani, Akbar, et al, 2018). The proponents of the institutional theory believe that an organization will not be able to achieve the substance expected from the policy adopted if it is not based on substantive goals.…”
Section: Introductionmentioning
confidence: 62%
“…Even though community participation and the competency of village management are high, if these two factors are not able to create good village fund management, then it would not contribute to a better village autonomy. This idea is in line with the perspective of the institutional isomorphism mechanism DiMaggio & Powell (1983) as further elaborated by (Sofyani, Akbar, et al, 2018). The proponents of the institutional theory believe that an organization will not be able to achieve the substance expected from the policy adopted if it is not based on substantive goals.…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, when they are demanded with higher performance targets in the current new university climate, such as research publication in reputable international journal, these old-generation lecturers need supervision and additional trainings. Sofyani et al (2018) explain that assistance (mentoring, supervision and training) and additional education, in this case in the form of science camp, is needed to improve employee's capability. Moreover, educations and programs alike can improve one's self-confidence to reach the targeted higher performance demand (Lovely, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The data are analyzed using thematic-deductive analysis approach suggested by Braun and Clarke (2006) and Sofyani, Akbar, and Ferrer (2018). This approach focuses on analyzing the structure of primary data obtained from the interview to find the general theme contained in the data.…”
Section: Codementioning
confidence: 99%
“…Much empirical research has highlighted the importance of the PMS and its role in achieving organisational objectives (Chenhall & Euske, 2007;Ferreira & Otley, 2009;Kallunki, Laitinen & Silvola, 2011;Riccaboni & Leone, 2010;Sofyani, Akbar & Ferrer, 2018). Spekle and Verbeeten (2014) also found that exploratory use of the PMS tends to enhance performance in public sector organisations.…”
Section: Public Sector Performance Measurement Systemmentioning
confidence: 99%
“…Hence, their evidence indicates that both alignment with the activities of the organisation and the way the PMS is used significantly affect organisational performance in the public sector. However, Sofyani et al (2018) claimed that despite the significant role of the PMS, its implementation in Indonesia has not achieved the full aim of improving performance and accountability.…”
Section: Public Sector Performance Measurement Systemmentioning
confidence: 99%